Deconstructing deficit perspectives on minority youth: a longitudinal analysis of South Korean adolescents' Korean and English proficiency. Issue 6 (2nd July 2020) - Shin, Jaran; Kim, Jinho
ABSTRACT: Drawing on ecological perspectives, this study examined the foundational assumption behind the negative stereotypes that surround children of mixed parentage in South Korea; namely, that their alleged deficiency in the Korean language will cause numerous issues for Korean society. The data used for this study came from a panel study of Korean adolescents that included such variables as their Korean and English proficiency as well as other explanatory variables at the individual, family, school, and community level. This study revealed that the longitudinal trajectories of Korean and English proficiency for mixed parentage adolescents were comparable to those of peers who had ethnically Korean parents. This suggests that the 'multicultural' label attached to this group of minority youth has served as a means of managing growing economic inequality exacerbated by globalization; in particular, the delusion of the label is highlighted by the strong bond between children's language proficiency and their socioeconomic status. The findings of this study urge researchers and educators to assess more critically the lives of minority children.